Formulasi Army Body Mist Minyak Serai Wangi (Citronella oil) sebagai Anti Repellent - Hendrik Hermawan; Gita Cahya Eka Darma; Ratih Aryani (UNISBA Press, 2024)
Abstract. Repellent is a material that has the ability to protect humans from mosquito bites when sprayed on the surface of the skin and clothing. One of the natural ingredients that has potential as repellant is citronella essential oil (Citronella oil) with the main compounds containing citronellal (24.33%), citronellol (11.34%) and geraniol (13.17%). Citronella essential oil is formulated in preparation of body mist. The aim of this research is to obtain a formula body mist fragrant lemongrass essential oil as an anti repellent against mosquitoes Aedes aegypti, to determine the length of time the fragrance of the preparation lasts and to determine the effectiveness of the preparation as repellent against mosquitoes Aedes aegypti, To obtain the right concentration of citronella essential oil, in this study solutions were made with different concentration variants from 5-15%. The results of the research carried out showed that the best formula was with the addition of citronella oil for 15% of the duration of the fragrance of the preparation body mist is in formula 3 because the fragrance lasts longer and the amount of citronella essential oil used is greater. Body mist which contains 10% citronella oil (F2) has the lowest perch power value compared to the formula 1.3, bergamot and distilled water (-). Abstrak. Repellant merupakan bahan yang memiliki kemampuan untuk melindungi manusia dari gigitan nyamuk bila disemprotkan ke permukaan kulit dan pakaian. Salah satu bahan alam yang berpotensi sebagai repellant adalah minyak atsiri serai wangi (Citronella oil) dengan kandungan senyawa utama sitronelal (24,33%), sitronelol (11,34%) dan geraniol (13,17%). Minyak atsiri serai wangi diformulasikan dalam sediaan body mist. Tujuan dari penelitian ini adalah untuk memperoleh formula body mist minyak atsiri serai wangi sebagai anti repellant terhadap nyamuk Aedes aegypti, untuk mengetahui lama waktu ketahanan wangi sediaan serta untuk mengetahui efektivitas sediaan sebagai repellent terhadap nyamuk Aedes aegypti, Untuk mendapatkan konsentrasi minyak atsiri serai wangi yang tepat, pada penelitian ini dibuat larutan dengan varian konsentrasi yang berbeda dari 5-15%. Hasil penelitian yang dilakukan didapatkan formula terbaik dengan penambahan minyak serai wangi sebesar 15% lama waktu ketahanan wangi sediaan body mist berada pada formula 3 karena waktu ketahanan wanginya lebih lama dan minyak atsiri serai wangi yang digunakan jumlahnya lebih banyak. Body mist yang mengandung minyak serai wangi 10% (F2) memiliki nilai daya hinggap paling sedikit dibandingkan dengan formula 1,3,bergamot dan aquadest (-).